Empowering women? An assessment of international gender policies in Bosnia - Pupavac, Vanessa (Taylor & Francis, 2005)
International policy-making promises to empower women in Bosnia through encouraging their participation in the political process, giving them voice in civil society and through providing enhanced opportunities for economic independence. This paper challenges these claims, suggesting that while a narrow echelon of young middle class urban professionals have benefited from international gender approaches, the prospects for ordinary Bosnian women have not. First, the paper considers international attempts to promote the political empowerment of women through quota mechanisms and support for women’s organisations operating in civil society. Secondly, the paper considers international policies intended to further the economic empowerment of women and how these relate to broader neo-liberal prescriptions for the post-war state. It concludes that international policies, in both the political and economic realms, contain fundamental limitations which look likely to frustrate the long-term advancement of women in Bosnia.